PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA KANTOR KELURAHAN DI WILAYAH KECAMATAN MANTIKULORE KOTA PALU - NINGSI, SRI WAYATI (Fakultas Ekonomi Universitas Tadulako, 2017)
This study aims to determine and analyze the influence of Motivation and Discipline Work simultaneously or partially affect the performance of employees at the village office in the District Mantikulore Palu. This study uses quantitative research which is a research that aims to explain the relationship between two or more variables with a sample of 99 employees and data analysis techniques used are multiple linear regression. The results of hypothesis analysis and testing can be concluded: (1) based on regression test results obtained sig. F of 0.00 <0.05. This means that the variables of Motivation and Work Discipline simultaneously have a significant effect on employee performance variable. (2) based on the regression test results obtained motivation variable has significance level t sig. 0.033 <? 0.05. It means that partially motivation variable has significant effect to employee performance variable. (3) based on regression test results obtained by motivation variable has significance level t sig. 0,000> ? 0.05. It means that partially variable of Work Discipline have significant effect to employee performance variable.